Temporal evolution of the magnetically active eclipsing binary DV Psc - Palafouta, S.; Gazeas, K. (Contributions of the Astronomical Observatory Skalnate Pleso, 2020)
The existence of magnetic activity on the eclipsing binary DV Psc has been known for almost two decades. However, until recently, no evidence of periodic behaviour relevant to this activity had been found. In this study, long-term photometric observations of DV Psc are used to analyze the system's magnetic activity, seek a possible magnetic cycle and determine orbital and physical parameters. The combination of photometric and spectroscopic observations results in a unified model that describes the system over time in terms of variable spot activity. New times of minimum light are determined and an accurate astronomical ephemeris and updated O-C diagram are constructed for a total span of 19 years (1997-2017). The intense magnetic activity, as indicated by strong asymmetries in the light curves (O' Connell effect), and the periodic variation of the O-C diagram are combined to explain the system's behaviour. The existence of a third body, orbiting the eclipsing binary in an eccentric orbit, as well as a magnetic cycle are the most likely scenario.
Keywords: binaries: close; binaries: eclipsing; stars: activity